STRUCTURE AND LAYERS MEANING OF ANGGINI WARRIOR’S COSTUME IN WIRO SABLENG (2018) - Puspitasari, Feny; Piliang, Yasraf Amir; Kahdar, Kahfiati; Waskita, Dana (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Different contexts suggest varying perspectives and interests of the filmmakers, which will influence the visual ideologies formed. One of the main ways filmmakers visually communicate their ideologies is through costumes. Costumes can be functional clothing and symbols that convey social-cultural and ideological messages. Costumes help shape how the audience perceives characters and their roles, revealing deeper meanings about identity, values, and worldviews. Previous research has explored how costumes contribute to character identity formation, focusing on roles, status, and psychological traits. This study adopts Roland Barthes’ semiotic analysis combined with content analysis. Barthes’ semiotic theory helps decode the denotative and connotative meanings of costumes. This approach aims to broaden the understanding of the meaning behind costumes as visual objects and to better interpret their role in conveying ideologies, especially concerning character representation, with case studies of Anggini characters in the Wiro Sableng (2018). This research reveals that Anggini's costume structurally holds multiple levels of meaning, from the functional and decorative purposes of clothing to the secondary meaning as a symbol of femininity, ethnicity, strength, and masculinity. The costume portrays Anggini as a symbol of strength and resilience and an empowered figure who challenges traditional gender roles in the film Wiro Sableng (2018).